Serotonin Deficiency Increases Context-Dependent Fear Learning Through Modulation of Hippocampal Activity - Waider, Jonas; Popp, Sandy; Mlinar, Boris; Montalbano, Alberto; Bonfiglio, Francesco; Aboagye, Benjamin; Thuy, Elisabeth; Kern, Raphael; Thiel, Christopher; Araragi, Naozumi; Svirin, Evgeniy; Schmitt-Böhrer, Angelika G.; et al. (Frontiers in Neuroscience, 2019)
Brain serotonin (5-hydroxytryptamine, 5-HT) system dysfunction is implicated in exaggerated fear responses triggering various anxiety-, stress-, and trauma-related disorders. However, the underlying mechanisms are not well understood. Here, we investigated the impact of constitutively inactivated 5-HT synthesis on context-dependent fear learning and extinction using tryptophan hydroxylase 2 (Tph2) knockout mice. Fear conditioning and context-dependent fear memory extinction paradigms were combined with c-Fos imaging and electrophysiological recordings in the dorsal hippocampus. Tph2 mutant mice, completely devoid of 5-HT synthesis in brain, displayed accelerated fear memory formation and increased locomotor responses to foot shock. Furthermore, recall of context-dependent fear memory and its extinction was increased. The behavioral responses were associated with increased c-Fos expression in the dorsal hippocampus and resistance to foot shock-induced impairment of hippocampal long-term potentiation (LTP). In conclusion, increased context-dependent fear memory resulting from brain 5-HT deficiency involves dysfunction of the hippocampal circuitry controlling contextual representation of fear-related behavioral responses.